Sertraline induced acute hepatocellular liver injury in patient with major depressive disorder: a case report - Renemane, Lubova; Rancans, Elmars (Frontiers in Psychiatry, 2024)
This case report describes a patient with major depressive disorder (MDD) who developed acute hepatocellular liver injury after being treated with sertraline, a selective serotonin reuptake inhibitor (SSRI). The diagnosis of MDD was made two years prior, and the patient had previously responded partially to escitalopram and cognitive-behavioral therapy (CBT). Upon switching to sertraline 50 mg daily, the patient presented with severe symptoms indicative of acute liver injury, including elevated liver enzymes, jaundice, and gastrointestinal distress. Following the discontinuation of sertraline, the patient's liver function tests gradually normalized over a 90-day period, confirming the diagnosis of sertraline-induced hepatotoxicity. This case underscores the importance of continuous monitoring for potential liver injury in patients treated with sertraline. The findings contribute to the existing body of evidence on the hepatotoxic risks associated with SSRIs and highlight the need for personalized treatment strategies to mitigate adverse effects and enhance patient safety. Further research is needed to explore the long-term safety and efficacy of sertraline, particularly in vulnerable populations.